Stock market cycles and supply side dynamics - Paul de Grauwe; Eddie Gerba (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2015)
The agent-based (behavioural) model is extended to include a financial friction on the supply side. Firms finance capital purchases using external financing, but need to pay for it in advance. In addition, firm financing constraint and net worth are determined by stock market prices, which can (and will) deviate from the fundamental value. The result is that production, supply of credit and the share that firms pay to capital producers heavily depends on the stock market cycles. During phases of optimism, credit is abundant, access to production capital is easy, the cash-in-advance constraint is lax, the risks are undervalued, and production is booming. But upon reversal in market sentiment, the contraction in all these parameters is deeper and asymmetric. This is even more evident in the behavioural model since cognitive limitations of economic agents result in exacerbation of the contraction. Lastly, the behavioural model matches much of the data, including the interest rate, inflation, firm credit, firm financing spread, and bank net worth. It is also successful in matching several supply-side relations (capital-firm credit, inflation-interest rate) as well as their autocorrelations. The results from the empirical validation are favourable to the behavioural model.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: B41; C63; C68; E22; E23; E37; 330; supply-side; beliefs; financial frictions; model validation